Dual functions of NME1 in suppression of cell motility and enhancement of genomic stability in melanoma - Kaetzel, David M. (Naunyn Schmiedebergs Arch Pharmacol, 2014)
The NME1 gene represents the prototypical metastasis suppressor, whose expression inhibits cell motility and metastasis without impact on primary tumor growth in a number of different human cancers. This report outlines our recent efforts to define the molecular mechanisms through which NME1 both suppresses cell motility and promotes genomic integrity in the setting of human melanoma. Forced NME1 expression in a variety of melanoma-derived cell lines was shown to induce dynamic changes in cell morphology and reorganization of the actin cytoskeleton, with formation of a network of thick stress fibers and assembly of fibronectin fibrils at large focal adhesions. Moreover, NME1 expression results in adhesion reprogramming through an impact on integrin repertoire and focal adhesion dynamics. Having previously demonstrated that NME1 expression promotes repair of DNA damage induced by ultraviolet radiation (UVR) in both yeast and mammalian cells, probably via the nucleotide excision repair pathway, we have more recently demonstrated that NME1 is rapidly recruited to double-strand breaks. This preliminary result represents the first evidence of direct interactions between NME1 and DNA in the context of DNA repair, and has set the stage for current efforts to probe its functional interactions with double-strand break repair pathways. Discussed herein are molecular models to explain the interactions of NME1 with such diverse cellular functions as cell motility and DNA repair, potentially through its nucleoside diphosphate kinase and 3′-5′ exonuclease activities.